1974
DOI: 10.1159/000136516
|View full text |Cite
|
Sign up to set email alerts
|

Protein Binding of Indomethacin: Binding of Indomethacin to Human Plasma Albumin and its Displacement from Binding by Ibuprofen, Phenylbutazone and Salicylate, <i>in vitro</i>

Abstract: The reversible binding of indomethacin to human plasmaprotein and the manner in which this may be modified by ibuprofen, phenylbutazone and salicylate was studied by ultrafiltration at 37 °C and pH 7.4. Indomethacin is much more highly bound than has previously been considered. The affinity constant for the single primary binding site is 3 x 105 l/mol and for the seven secondary binding sites 1.4 x 104 l/mol. The protein binding of indomethacin is increased by the presence of phenylbutazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

1975
1975
2005
2005

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Using the published pharmacokinetic parameters of indomethacin in rats (Ogiso et al, 1989), the starting plasma concentration (C 0 ) of indomethacin at the dose given in this study is predicted to be 83.3 g/ml. Given that indomethacin is about 90% bound in plasma (Mason and McQueen, 1974), the free concentration of indomethacin would be 8.3 g/ml. It has also been shown that indomethacin can interact with MRP4 at a concentration low as 0.375 g/ml (1 M) (Reid et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Using the published pharmacokinetic parameters of indomethacin in rats (Ogiso et al, 1989), the starting plasma concentration (C 0 ) of indomethacin at the dose given in this study is predicted to be 83.3 g/ml. Given that indomethacin is about 90% bound in plasma (Mason and McQueen, 1974), the free concentration of indomethacin would be 8.3 g/ml. It has also been shown that indomethacin can interact with MRP4 at a concentration low as 0.375 g/ml (1 M) (Reid et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Mason and McQueen [ 13] have measured indomethacin binding to pooled adult human plasma with a known content of albumin. Our binding isotherm is consistent with the one reported by these authors confirming the validity of the experimental observations.…”
Section: Discussionmentioning
confidence: 99%
“…It is not necessarily valid to translate directly the results of experiments done in vitro to the situation in vivo. Nevertheless, it is worth mentioning that concentrations of indomethacin were much in excess of those needed (0.1 jg/ml) to inhibit ACTH-induced prostaglandin release in vitro from adrenal cortical cells of the cat (Laychock & Rubin, 1976), even accounting for protein binding of indomethacin (-90% in man; Mason & McQueen, 1974).…”
Section: Discussionmentioning
confidence: 99%